Bactericidal activity of alpha-bromocinnamaldehyde against persisters in Escherichia coli - Shen, Qingshan; Zhou, Wei; Hu, Liangbin; Qi, Yonghua; Ning, Hongmei; Chen, Jian; Mo, Haizhen (PLOS ONE, 2017)
Persisters are tolerant to multiple antibiotics, and widely distributed in bacteria, fungi, parasites, and even cancerous human cell populations, leading to recurrent infections and relapse after therapy. In this study, we investigated the potential of cinnamaldehyde and its derivatives to eradicate persisters in Escherichia coli. The results showed that 200 μg/ml of alpha-bromocinnamaldehyde (Br-CA) was capable of killing all E. coli cells during the exponential phase. Considering the heterogeneous nature of persisters, multiple types of persisters were induced and exposed to Br-CA. Our results indicated that no cells in the ppGpp-overproducing strain or TisB-overexpressing strain survived the treatment of Br-CA although considerable amounts of persisters to ampicillin (Amp) and ciprofloxacin (Cip) were induced. Chemical induction by carbonyl cyanide m-chlorophenylhydrazone (CCCP) led to the formation of more than 10% persister to Amp and Cip in the entire population, and Br-CA still completely eradicated them. In addition, the cells in the stationary phase, which are usually highly recalcitrant to antibiotics treatment, were also completely eradicated by 400 μg/ml of Br-CA. Further studies showed that neither thiourea (hydroxyl-radical scavenger) nor DPTA (Fe3+ chelator to block the hydroxyl-radical) affected the bactericidal efficiency of the Br-CA to kill E. coli, indicating a ROS-independent bactericidal mechanism. Taken together, we concluded that Br-CA compound has a novel bactericidal mechanism and the potential to mitigate antibiotics resistance crisis.